The Relationship Between Nutritional Status and the Incidence of Simple Febrile Seizure in Children - Ridwan, Nasywa Zahra; Yenny, Yenny (Oshada, 2026)
Simple febrile seizures are brief, generalized seizures lasting less than 15 minutes without recurrence within 24 hours. Nutritional status has been proposed to influence immune function and susceptibility to infection, which may trigger fever. However, evidence regarding its association with simple febrile seizures remains inconsistent. This study aimed to assess the relationship between nutritional status and simple febrile seizures in children. This study was an observational analytic study with a cross-sectional approach conducted at dr. Bratanata level III Hospital Jambi, Indonesia from January to November 2025. A total of 160 children who met the inclusion criteria were recruited through consecutive non-random sampling, with data on nutritional status assessed using anthropometric measurements based on WHO growth standard and the incidence of simple febrile seizures obtained from medical records. Data were analyzed using the Chi-square test to evaluate the association between nutritional status and simple febrile seizures, with p<0.05 considered statistically significant. The prevalence of simple febrile seizures among the study population was 85 (53.1%) of the children, whereas 75 (46.9%) of the children had fever without seizures. There is no association between the nutrition status and occurrence of simple febrile seizures (p=0,242). Further longitudinal studies incorporating micronutrient assessment are recommended to explore the potential role of hidden hunger